Market efficiency and international linkage of stock prices: An analysis with high-frequency data - Yoshiro Tsutsui; Kenjiro Hirayama (Osaka University, Institute of Social and Economic Research (ISER), 2004)
This paper uses one-minute returns on the TOPIX and S&P500 to examine the efficiency of the Tokyo and New York Stock Exchanges. Our major finding is that Tokyo completes reactions to New York within six minutes, but New York reacts within fourteen minutes. Dividing the sample period into three subperiods, we found that the efficiency has improved and the magnitude of reaction has become larger over the period in both markets. The magnitude of response in New York to a fall in Tokyo is roughly double that of a rise.
Keywords: G14; G15; F36; 330; international linkage; stock prices; market efficiency; high frequency data; Internationaler Finanzmarkt; Börsenkurs; USA; Japan; Effizienzmarkthypothese